2019
DOI: 10.1007/s11367-019-01675-x
|View full text |Cite
|
Sign up to set email alerts
|

Recommendation and context: the missing links for increased life cycle impact in large industries

Abstract: Purpose This study takes an open and explorative approach to investigating the impact, or lack of impact, of life cycle information on behaviours throughout large production companies. Based on cases where life cycle information has been provided, this paper analyses how life cycle information has been interpreted and acted upon—not only by the life cycle assessment (LCA) practitioner conducting the study but also by employees outside the environmental departments. Methods To understand the impact of life cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…The Centre is developing methods, tools and working practices via collaborative research projects, through case studies, in working groups and in round-table discussions. Some of these have resulted in the integration of life cycle assessment into product development processes [9,10], supply-chain management in purchasing [11], logistics planning [12], better understanding of recycling [13,14], and decision support being adopted for different business functions [15]. It has also resulted in better knowledge on life cycle thinking in environmental management systems [16], better understanding of policy initiatives and how they will affect various organisations such as the Product Environmental Footprint (an initiative of the European Commission) [17,18].…”
Section: Methods Tools and Working Practicesmentioning
confidence: 99%
“…The Centre is developing methods, tools and working practices via collaborative research projects, through case studies, in working groups and in round-table discussions. Some of these have resulted in the integration of life cycle assessment into product development processes [9,10], supply-chain management in purchasing [11], logistics planning [12], better understanding of recycling [13,14], and decision support being adopted for different business functions [15]. It has also resulted in better knowledge on life cycle thinking in environmental management systems [16], better understanding of policy initiatives and how they will affect various organisations such as the Product Environmental Footprint (an initiative of the European Commission) [17,18].…”
Section: Methods Tools and Working Practicesmentioning
confidence: 99%
“…These issues have also been addressed relating to the use of LCA‐information. For example, Rex, Fernqvist, and Ryding (2020) indicated that further guidance is needed for the interpretation of the results from an LCA study, and Sala and Andreasson (2018) pointed out that the results need to be presented and visualized better and in understandable ways. Considering that ISO 14025 states that EPD‐information is primarily intended for business‐to‐business communication, but nevertheless its use for business‐to‐consumer communication is also foreseen (ISO, 2006a), it emphasizes the need to improve interpretation and the understanding of the results, especially when aimed at an audience without much knowledge about LCA.…”
Section: Introductionmentioning
confidence: 99%